Signage Design “Fuadah” as An Effort to Unify Diversity in Salatiga - Dwijayanti, Ita (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2023)
As the only state university in Salatiga, Universitas Islam Negeri (UIN) Salatiga strives to be a reference laboratory for moderate Islamic Studies in Salatiga as well as Indonesia. Although UIN Salatiga has a faculty that specializes in moderate Islam, named Faculty of Ushuluddin, Adab, and Humanities (FUADAH), the data shows that only 11% of students over 5 other faculties are interested and study there. The preliminary study done by the researcher implies the lack of socialization in the form of signage design for branding. This research aims to present and explain a